2010
DOI: 10.1021/je100248m
|View full text |Cite
|
Sign up to set email alerts
|

Single and Binary System Dye Removal from Colored Textile Wastewater by a Dendrimer as a Polymeric Nanoarchitecture: Equilibrium and Kinetics

Abstract: This paper deals with the removal of textile dyes from aqueous solutions by a poly(propylene imine) dendrimer (PPI) as a polymeric nanoarchitecture in single and binary (mixture of dyes) systems. Direct Blue 78 (DB78) and Acid Black 26 (AB26) were used as model dyes. The effects of operational parameters such as dendrimer concentration, contact time, dye concentration, inorganic anions (salts), and pH have been studied on dye removal. Adsorption isotherms (Langmuir, Freundlich, and Tempkin models), adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(32 citation statements)
references
References 64 publications
1
31
0
Order By: Relevance
“…These results revealed that the dye uptake increased with increasing temperature from 20 to 100 °C. In particular, as suggested from literature, at higher temperature, the mobility of dyes is expected to increase. Additionally, a swelling effect of the internal structure of the hydrogel occurs, enabling the large dye molecules to penetrate into the structure in higher quantities.…”
Section: Resultsmentioning
confidence: 64%
“…These results revealed that the dye uptake increased with increasing temperature from 20 to 100 °C. In particular, as suggested from literature, at higher temperature, the mobility of dyes is expected to increase. Additionally, a swelling effect of the internal structure of the hydrogel occurs, enabling the large dye molecules to penetrate into the structure in higher quantities.…”
Section: Resultsmentioning
confidence: 64%
“…The environmental problems related to the textile industry are numerous and well documented (Mahmoodi et al, 2010a;Mahmoodi et al, 2010b;Gottipati and Mishra, 2010;Lima et al, 2007;Epolito et al, 2005). Besides the removal of organic loads, blue color removal is one of the main objectives in the treatment of textile effluents.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the dyes and pigments are harmful to aquatic and human life because of their toxic, carcinogenic, mutagenic and teratogenic properties [6]. Therefore, the government and concerned authorities have established various environmental standards on the quality of effluent before discharging into the environment and this constrained the industries to remove dyes from their effluents before discharging [7].…”
Section: Introductionmentioning
confidence: 99%